Characteristics of Cold Wounds Under Therapy With Cryopreserved Cord Blood Serum - Ischenko, Irina O.; Vlasov, Aleksandr A.; Kovalev, Gennadiy A.; Naumova, Olga V.; Sandomirsky, Boris P. (Problems of Cryobiology and Cryomedicine, 2015)
N/A